Analisis Analisis Ratio Free Float, Risiko Likuiditas, dan Risiko Keuanganpada Return Saham Indeks IDXV 30 Tahun 2020-2021 - Nekky Rahmiyati; Anggit Anggrahito (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
The objective of this research is to investigate how three factors impact the outcome, namely free ï¬‚oat ratio, liquidity risk, and ï¬nancial risk on the stock returns of the IDXV 30 index in 2020-2021. The information utilized in this research were acquired as secondary data from IDX during the period of January 2020 to December 2021. The technique utilized for analyzing the data was multiple linear regression. The results of the study indicate that there is a simultaneous eï¬€ect between free ï¬‚oat ratio, liquidity risk, and ï¬nancial risk on stock returns in the IDXV 30 index in 2020-2021. This study also shows that liquidity risk has a greater inï¬‚uence on stock returns than free ï¬‚oat ratio and ï¬nancial risk inthe IDXV 30 index in 2020. The results of this study can provide important contributions to investors in making investment decisions in the IDXV 30 index in 2020-2021. Investors canpay attention to liquidity risk as one of the factors that can aï¬€ect the stock returns of the IDXV 30 index. Furthermore, this study can also serve as a reference for future researchers in developing research on the inï¬‚uence of certain factors on stock returns of the index.